Teaching Alphabet for Young Learners through Song - Mira Yeni; Rosmalita Amelia (Universitas Pahlawan Tuanku Tambusai, 2020)
Teaching young learners is not a straight forward job. Then, vocabulary is central of teaching and learning. Copying with the characteristic of young learner students, song is one amongst applicable ways in which to form an honest atmosphere to form teaching and learning method contemporary and attention-grabbing. Teaching alphabet of young learners through song can describe the benefits of song to support English language learning method and conjointly review some strategies to use songs in English room. This research described a case for the position of English language in country and therefore the characteristic of young learner as foreign language learners. Songs area unit learning resources that have numerous blessings, as well as linguistics resource, affective/psychological resource, and psychological feature resource. Songs can also be used as a media to show four major skills, that area unit speaking, reading and writing. Another language ability like pronunciation, vocabulary and synchronic linguistics may be learnt with the utilization of songs yet. Songs may be smart learning sources for English language category. It might be higher if English language academics in elementary colleges understand the benefits of victimization songs within the learning method to boost the standard of English language learning method.